Growth and Fresh Biomass Responses of Red Onions (Allium ascalonicum L.) to Banana Stem Compost (Musa paradisiaca) - Yusup Hasim; Umi Kulsum Nur Qomariah; Mazidatul Faizah (AGARICUS: Advances Agriculture Science & Farming, 2026)
To identify the effectiveness of introducing liquid organic fertilizer (POC) made from banana stems, this study examined the dynamics of several shallot vegetation indicators, including plant height, leaf quantity, and fresh weight. The study was conducted from October to December 2025 at the experimental site in Denanyar Village, Jombang Subdistrict, Jombang Regency, East Java. This study employed a quantitative methodology based on a Completely Randomized Design (CRD). This method applied six treatments: P0 (Control), P1 (Application of 75 ml/L banana stem POC), P2 (application of 150 ml/L banana stem POC), P3 (application of 225 ml/L banana stem POC), P4 (application of 300 ml/L banana stem POC), and P5 (application of 375 ml/L banana stem POC). The application of banana stem liquid organic fertilizer (POC) was found to have no significant effect on the vegetative performance of shallot plants. This was confirmed by an analysis of variance (ANOVA) on the parameters of plant height (calculated F = 1.10 < 5% critical F = 2.38), leaf area (calculated F = 0.53 < 5% critical F = 2.38), and fresh weight (calculated F = 1.16 < 5% critical F = 2.38), where all calculated F values did not exceed the critical F threshold at the 5% significance level. The absence of these statistical differences confirms that the application of liquid organic fertilizer has not yet been able to significantly influence plant growth dynamics.